Colonial subjects : Puerto Ricans in a global perspective - Grosfoguel, Ramón (University of California Press, 2003)
Colonial Subjects is the first book to use a combination of world-system and postcolonial approaches to compare Puerto Rican migration with Caribbean migration to both the United States and Western Europe. Ramon Grosfoguel provides an alternative reading of the world-system approach to Puerto Rico's history, political economy, and urbanization processes.